The Effect of Science Process Skills-based Worksheet to Improve Creative Thinking of High School Physics Students in Indonesia - Purnama, Epi; Abdullah, Helmi; Arafah, Kaharuddin; Sanam, Anna Isabela (Jurnal Pendidikan Progresif, 2024)
The Effect of Science Process Skills-based Worksheet to Improve Students' Creative Thinking Skills in Physics Learning. Objective: This study aimed to examine the effect of using SPS-Based Worksheet on improving students' creative thinking skills in learning Physics. Methods: Experimental method was implemented using non-equivalent control group design, involving 30 high school students who were divided into experimental class and control class. Data analysis was conducted using t-test to compare the average improvement of creative thinking skills between the two groups, as well as ANOVA to measure differences in achievement based on students' ability levels. Findings: The results showed that students in the experimental class had a significant improvement in creative thinking skills compared to students in the control class. Based on the analysis of creative thinking indicators, it was found that the experimental class showed significant improvement in all indicators, namely fluency, originality, flexibility, and elaboration, with the highest contribution in the originality indicator. In addition, result of ANOVA test showed that students' ability level had a significant influence on the achievement on each indicator, where students with higher ability level showed more consistent achievement on all indicators. Conclusion: This study shows that the use of SPS-Based Worksheet is effective in improving students' overall creative thinking skills, especially in science process skills, and in learning Physics. Keywords: student worksheets, science process skills, creative thinking skills, physics.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024112